O desempenho físico, o estado humoral e a rotina de sono perante as cargas de treinamento aplicadas com atletas de futebol em idade escolar da cidade de Aguiarnópolis-TO. - Miranda, Kennedy Pereira (Universidade Federal do Tocantins, 2019)
The study aimed to verify the physical performance, humoral state and sleep routine before the training loads applied to soccer athletes of school age in the city of Aguiarnópolis-TO. It is characterized as a descriptive and cross-sectional qualitative- quantitative study. The sample was comprised of 24 athletes / students and a teacher / technician from a soccer school in this municipality. Taking into account the following inclusion criteria: students aged between 13 and 17 years, male, practicing routine training for competition for at least six months and enrolled in municipal schools. The research tools used with school-age soccer athletes were: the Profile of Mood States (POMS) Questionnaire to measure the humoral profile state, the Sleep Questionnaire to verify sleep routine and the Rast test for power analysis anaerobic that verifies the level of physical performance. The research instrument applied to the technician was the training monitoring score to verify the training routine of the athletes, which was developed specifically for this research. When evaluating the loads applied and how training was monitored, we observed that the athletes presented physiologically below-expected responses, since the maximum and average power indices were weak and the high fatigue index, than expected for footballers in this age group. However, the psychometric tests revealed that the athletes were feeling psychologically with an adequate state of humor, besides good quality of sleep, which usually are affected in situation of psychophysiological wear. All ethical steps were taken to carry out this research. It was concluded that the training loads imposed on the athletes at the time of evaluation were generating low rates of physical performance, however, with no noticeable changes in the mood and sleep routine of school-age soccer athletes during the research. Thus, despite the low performance indexes, the fact that the psychological profile is adequate indicates that the athletes are in a good state and that from the monitoring of the applied loads can have their performances optimized.